2015
DOI: 10.1111/ajps.12203
|View full text |Cite
|
Sign up to set email alerts
|

When Are Monetary Policy Preferences Egocentric? Evidence from American Surveys and an Experiment

Abstract: This article enters the international/comparative political economy debate about whether individual-level macroeconomic policy preferences are egocentric and, if so, on what basis (factors, sectors, or firms). It argues that contextual information may function as a precondition for the emergence of egocentric preferences. With a focus on the trade-off between using monetary policy for a domestic or an international goal, it presents evidence from three original American surveys using informative vignettes to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…Hermann 2017. 45. For work on the connection between economic knowledge and preferences in these policy domains, see Bearce and Tuxhorn 2017;Prather 2015;and Tomz 2004;but compare Curtis, Jupille, and Leblang 2014. 46. See, for example, Chwieroth and Sinclair 2013;and Drezner and McNamara 2013. from paying sufficient attention to the role of prevailing ideas.…”
Section: Resultsmentioning
confidence: 99%
“…Hermann 2017. 45. For work on the connection between economic knowledge and preferences in these policy domains, see Bearce and Tuxhorn 2017;Prather 2015;and Tomz 2004;but compare Curtis, Jupille, and Leblang 2014. 46. See, for example, Chwieroth and Sinclair 2013;and Drezner and McNamara 2013. from paying sufficient attention to the role of prevailing ideas.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, for benchmarking economic self-interest in immigration policy, scholars use a factor proportions model, in which natives face labor market competition against immigrants with similar skill level (often measured by educational attainment). For benchmarking economic self-interest in the monetary policy domain, Bearce & Tuxhorn (2017) base their measurements of covariates on the factor-, sector-, and firm-based models of monetary policy preferences (to be discussed in detail below).…”
Section: Testing Preference Formation I: Materials Versus Nonmaterials mentioning
confidence: 99%
“…By contrast, the bulk of findings from survey experiments lend support for noneconomic sources of support for protectionism, such as other-regarding preferences (Naoi & Kume 2011, Lü et al 2012, Chilton et al 2020, nationalism, and ethnocentrism (Margalit 2012, Mansfield & Mutz 2013. In fact, survey experimental studies have rarely found support for economic self-interest as a driver of opposition to globalization [exceptions include studies by Rho & Tomz (2017) and Bearce & Tuxhorn (2017), which I discuss in detail below]. Furthermore, these findings from survey experiments corroborate the findings from nationally representative public opinion data that the salience of trade and other globalization-related issues has been extremely low in the public mind, even at the height of the China import shock (mid-2000s; see Guisinger 2009Guisinger , 2017Cramer 2016) and during the Great Recession, the largest economic contraction since the Great Depression (Naoi 2018).…”
Section: Introductionmentioning
confidence: 99%
“…3 Among many, see Dietrich (2013), Bush (2015), Reinsberg (2015), and Winters & Martinez (2015). 4 See examples concerning immigration policy (Scheve & Slaughter 2001a, Facchini & Mayda 2009, trade policy (Scheve & Slaughter 2001b, Hays, Ehrlich & Peinhardt 2005, monetary policy (Bearce & Tuxhorn 2017), economic sanctions (Heinrich, Kobayashi & Peterson 2016), diplomacy (Tanaka 2015), counterterrorism (Garcia & Geva 2016), and the use of the military (Tomz & Weeks 2013, Johns & Davies 2014.…”
mentioning
confidence: 99%